Food and snow intake, body mass and rumen function in reindeer fed lichen and subsequently starved for 4 days - Aagnes, T.H.; Mathiesen, S.D. (Rangifer, 1994)
Food and snow intake, body mass, rumen fluid volume, rumen fluid turnover time and ruminal dry matter content were examined in four female rumen fistulated reindeer which were first fed lichen ad libitum in 14 days and then starved for 4 days in March. When the animals were eating lichen median daily dry matter food intake was 15.7 g/kg (range 12.2-19.9 g/kg), while median daily snow intake only amounted to 0.6 g/kg (range 0-3.3 g/kg). The median body mass decreased from 67.5 kg (range 62.5-69.5 kg) to 63.5 kg (range 60.5-68.5 kg) during this period, and dropped further to 62.5 kg (range 57.5-66.0 kg) after four days of starvation. Rumen fluid volume and fluid turnover time were fairly constant in individual animals, but varied between animals fed lichen ad libitum. Neither of these parameters changed significantly (P>0.05), but ruminal dry matter decreased, while snow intake rose conspicuously in reponse to starvation. Thus, aside from the latter, which mitigate the reduction of total rumen volume, we have failed to expose any special adaptions aimed at the maintenance of ruminal integrity in starving reindeer.